An archaeological examination of the Baumann site - a precontact Lalonde settlement in Simcoe County, Ontario - Stopp, Marianne P. (1982)
Thesis (M.A.) -- Memorial University of Newfoundland, 1982. Anthropology Bibliography : leaves 122-128.